Facebook as an instrument of election campaigning and voters' engagement: Comparing Czechia and Poland. (April 2019) - Stetka , Vaclav; Surowiec, Paweł; Mazák, Jaromír
Adding to the growing scholarship on the use and role of social media in election campaigning, this article examines and compares the character and determinants of Internet users' engagement with political party communication in 2013 and 2015 Parliamentary election campaigns in Czechia and Poland. Apart from the relationship between the thematic focus of party-produced content and the level of users' interactivity, the study also explores the way the tonality of users' comments is influenced by different types of party communication, as well as by users' gender. The results suggest that the level of support for a party status is largely independent of the content of the message in both countries. The type of content has, however, an effect on the intensity of criticism by the users, with policy-related subjects generating more negativity than mobilization- or campaign-oriented statuses. Finally, the study points to both gender gaps and gender as a strong predictor of user negativity, as female users – while constituting a minority of participants in both countries – tend to be significantly less negative in their comments towards the home party. Overall, the comparative study reveals both similarities and differences in the way Czech and Polish parties utilize Facebook as campaign platform, as well as in their respective Internet users' engagement with parties messages.